Plasma Metanephrines Are Associated With Glucose Metabolism in Patients With Essential Hypertension. Issue 37 (September 2015) - Wang, Weiqing; Mu, Liangshan; Su, Tingwei; Ye, Lei; Jiang, Yiran; Jiang, Lei; Zhou, Weiwei; Carrillo., Jose Zacarias Parra
<x xml:space="preserve">Abstract</x> Abstract There is a high incidence of glucose intolerance in essential hypertension. Overactivation of the sympathetic system is one of important causes of essential hypertension. Whether sympathetic system affects glucose metabolism in patients with essential hypertension has never been reported previously. The aim of this study was to explore the association between the sympathetic system activity and glucose metabolism in patients with essential hypertension. A total of 202 essential hypertension inpatients without diabetes were recruited from Shanghai Ruijin Hospital between February 2006 and August 2013. Activity of sympathetic system was quantified by plasma metanephrines (MNs) levels. All subjects received an oral glucose tolerance test. Fasting plasma glucose and 2-hour plasma glucose increased significantly across the quartiles of plasma MNs. The multiple linear regression analysis revealed that plasma MNs were significantly associated with fasting plasma glucose and 2-hour plasma glucose. The area under curve of plasma glucose increased significantly from the lowest plasma MNs quartile across to the highest quartile. The multiple logistic regression analysis revealed that odds ratios (95% confidence interval) for prediabetes in the highest quartile compared with the lowest quartile of plasma MNs was 4.00 (95% confidence interval, 1.16–13.86). Plasma MNs levels are positively associated with plasma glucose in patients with essential hypertension. Patients with high plasma MNs levels had an increased risk of prediabetes.